Experimental Study on Properties of Concrete Using Ceramic Waste as Fine Aggregate and Steel Fiber as Coarse Aggregate (International Journal of Innovative Research in Computer Science & Technology, 2023)
Due to the day to day innovations and  development in construction field, the use of natural  aggregates is increased tremendously and at the same time,  the production of solid wastes from the demolitions of  constructions is also quite high. Because of these reasons  the reuse of demolished constructional wastes like ceramic  tile and granite powder came into the picture to reduce the  solid waste and to reduce the scarcity of natural aggregates  for making concrete. The ceramic tile waste is not only  occurring from the demolition of structures but also from  the manufacturing unit. The investigation finds out with the  partially replacement of fine aggregate with ceramic waste  and steel fiber with coarse aggregate in the concrete mix of  M30 was made and fresh and hardness test were examined  after 7 and 28 days. The investigation was achieved on  cement concrete in which partially replacement of fine  aggregate at percentage of 0%, 5%, 10%, 15% and 20%  with ceramic waste and steel fiber with coarse aggregate at  a percentage of 0%, 10%, 20% and 30% in M30 grade of  concrete respectively.
Keywords: Ceramic waste; Steel fibre; Compressive strength; slump test; Split Tensile strength; Abrasion test